(untitled) (ARQUISUR Revista, 2012)
Within the main strategies of the Modern Movement, a thing that insistently appears is the so-called ’planning in section’: housing rooms enclosed in vertically-displaced story buildings. Resorting to Wells Coates’ words, the traditional flat apartment has evolved into other models, with distinct single-story not flat solutions. Such strategy brought multiple advantages, from higher space efficiency, by reducing the collective flow of people, to the minimization of noise level transmission from between adjacent rooms. The most classic model is likely that of Unité d’Habitation de Marseille (1947-52), by Le Corbusier, but before and after that, several models were built, a lot of them in America, boasting geometries even more intricate and complex. Several of such models are presented, as well as the thought behind them, seeking particularly the ones publicized in reviews, showing a certain common working line in that dates.